High-effectively degrade the di-(2-ethylhexyl) phthalate via biochemical system: Resistant bacterial flora and persulfate oxidation activated by BC@Fe3O4. (July 2020) - Xie, Yanluo; Liu, Huakang; Li, Hao; Tang, Hao; Peng, He; Xu, Heng
Abstract: Di-(2-ethylhexyl) phthalate (DEHP) has been classified as a priority pollutant which increased the healthy risk to human and animals dramatically. Hence, a novel biochemical system combined by DEHP-resistant bacterial flora (B) and a green oxidant of persulfate (PS) activated by Nano-Fe3 O4 was applied to degrade DEHP in contaminated soil. In this study, the resistant bacterial flora was screened from activated sludge and immobilized by sodium alginate (SAB). Nano-Fe3 O4 was coated on biochar (BC@Fe3 O4 ) to prevent agglomerating in soil. X-ray diffraction (XRD) and scanning electron microscope (SEM) were utilized to characterize BC@Fe3 O4 . Results demonstrated that the treatment of biochemical system (SAB + BC@Fe3 O4  + PS) presented the maximum degradation rate about 92.56% within 24 days of incubation and improved soil microecology. The 16S rDNA sequences analysis of soil microorganisms showed a significantly different abundance and a similar diversity among different treatments. Kyoto Encyclopedia of Genes and Genomes (KEGG) functional genes difference analysis showed that some metabolic pathways, such as metabolism of cofactors and vitamins, energy metabolism, cell growth and death, replication and repair, were associated with the biodegradation of DEHP. Besides, DEHP was converted to MEHP and PA by biodegradation, while DEHP was converted to DBP and PA by persulfate and BC@Fe3 O4, and then ultimately degraded to CO2 and H2 O. Graphical abstract: Image 1 Highlights: The first time to apply Na2 S2 O8 activated by BC@Fe3 O4 to degrade DEHP in soil. Overcoming the problem that Fe3 O4 can't be homogeneously dispersed due to aggregation in soil. Studying the different DEHP-degrading pathways between chemical degradation and biodegradation.